Communication and information technologies annual - Cotten, Sheila R.; Robinson, Laura; Schulz, Jeremy (Studies in media and communications ;, 2014)
Sponsored by the Communication and Information Technologies Section of the American Sociological Association, this volume brings together nine studies of mediated childhood and youth. The studies shed light on the emerging contours of young people's web engagements and social practices. More specifically, the volume contains research speaking to scholarship dealing with four key topics: digital differentiation, media use, social problems, and cyberbullying. In the first section, authors address timely topics about social inequalities arising from unequal web use among children and teens. In the following section, the contributions reveal decision making processes about negotiating mediated communication by college students in Finland and the United States. Subsequently, in section three, the research offers solutions to social problems created by online threats and ever expanding advertising targeting children. Finally, the volume closes with research on cyberbullying as a moral panic and upstanders who stand up to cyberbullies. Taken together, the contributions raise far-reaching questions about how childhood and young adulthood is mediated and shaped by digital experiences.